Village Officials and Accountable Governance of Village Funds for SDGs 8 - Siti Fatikhatur Riskiyah; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village fund governance is central to strengthening local development and achieving Sustainable Development Goals (SDGs), particularly inclusive economic growth. Specific Background: In Indonesia, large fiscal transfers to villages demand transparent and accountable management by village officials to prevent misuse and ensure community benefits. Knowledge Gap: Existing studies often emphasize administrative compliance, while limited attention is given to how village officials operationalize transparency and accountability within local socio-institutional contexts. Aims: This study examines the role of village officials in managing village funds transparently and accountably as part of SDGs Goal 8 implementation. Results: Using a qualitative case study in Tambak Kalisogo Village, findings show that transparency is practiced through participatory budgeting, public reporting, and digital financial systems, while accountability is reinforced by multi-level reporting, community oversight, and institutional collaboration. Novelty: The study highlights a governance practice that integrates formal regulations with participatory and digital mechanisms at the village level. Implications: These findings suggest that strengthening institutional capacity and community involvement is essential for sustainable and inclusive village economic development aligned with SDGs 8.